Secure Cloud Native Microservices Architecture with Zero Trust Network Access Controls and Multi Layered Encryption for Resilient Distributed Systems - Lukman Medriavin Silalahi; Imelda Uli Vistalina Simanjuntak; Hayadi Hamuda; Irfan Kampono; Agus Dendi Rochendi; Abdul Hamid (Asosiasi Pengelola Jurnal Informatika dan Komputer Indonesia, 2026)
The increasing adoption of cloud native microservices has brought about significant improvements in scalability, flexibility, and resilience. However, these advancements also introduce substantial security challenges, particularly in distributed environments where traditional perimeter-based security models prove inadequate. This paper proposes a secure architecture for cloud native microservices that integrates Zero trust Network Access (ZTNA) and multi layered encryption techniques to address these security concerns. The architecture operates on the principle of